Pengaruh Motivasi Kerja dan Keadilan Organisasi terhadap Kualitas Kerja Pegawai BPS Kab Sukoharjo - Tia Ferliana Nur Aini; Agus Suyatno; Khabib Alia Akhmad; Umi Hanifah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the influence of work motivation and organizational justice on employee work quality at the Central Statistics Agency (BPS) of Sukoharjo Regency. A quantitative approach employing a causal-associative research design was applied to analyze the relationships among the research variables. The study population consisted of 40 employees, all of whom were selected as research respondents using a saturated sampling technique. Primary data were collected through structured questionnaires based on a five-point Likert scale and analyzed using multiple linear regression with SPSS version 25. The findings indicate that both work motivation and organizational justice have a positive and statistically significant effect on employee work quality, both individually and simultaneously. Employees with higher levels of motivation tend to demonstrate greater enthusiasm, discipline, responsibility, and punctuality in completing their tasks. Likewise, organizational justice enhances employees’ perceptions of fairness in decision-making, rewards, and workplace interactions, thereby strengthening trust, organizational commitment, and job satisfaction. These conditions collectively contribute to improved employee performance and work quality. Therefore, strengthening organizational justice while fostering employee motivation can serve as an effective strategy for improving work quality and supporting organizational performance at BPS Sukoharjo Regency.